Risk Management on Print Checking of Plastic Sacks Production in Sidoarjo Indonesia - Rizqy Kartika Sari; Denny A. Wahyudiono (Universitas Airlangga, 2020)
Introduction: Risk management is a management activity that aims to reduce risk to prevent negative impact. Calculation of the amount of risk was carried out to then determine whether the risk was acceptable. In printing activities, contact between humans and machines is unavoidable. The purpose of this study was to evaluate the risk of occupational safety management in the activity of print checking on stamping stage of plastic sacks production in Sidoarjo, Indonesia by conducting hazard identification, risk assessment which includes risk analysis and risk evaluation, control assessment, and residual risk assessment. This is an observational study with a cross sectional design. Methods: Data included primary and secondary data. Primary data were taken by interview and observation. Secondary data were taken from work accident data. Results: A total of 6 hazards were identified. Risk assessment recorded 2 low hazards category 2 medium hazards category, and 2 high risk hazards. Administrative control in the form of inspection and the use of PPE (Personal Protective Equipment) were implemented. Residual risk assessment shows that the implementation of controls was not optimal. The results of the residual risk assessment indicate that several risk categories fell into a lower category i.e 4 low hazards category and 2 high risk category hazards. Conclusion: The applied risk management has not been optimally implemented. It is recommended that the implementation of inspections is scheduled and a system for recording and reporting inspection findings is established. Keywords: hazard, printing checks, risk management